(untitled) (World Science, 2021)
To achieve the aim there has been examined 104 children aged 1–3 years with moderate and severe forms of intestinal infection of rotavirus etiology, for which they received appropriate treatment in Kharkiv Regional Children’s Infectious Diseases Clinical Hospital. Patients were divided into 2 groups: 1 group — 33 children with no concomitant herpesvirus, and 2 groups — 71 patients with rotavirus gastroenteritis and latent herpesvirus infection, caused by cytomegalovirus, Epstein-Barr virus or human herpes virus 6. Children in examined groups were comparable by gender, age, severity of main disease and other parameters. Prognosis of latent herpesvirus infection was made by means of multiple binomial regression. Independent predictors of concomitant herpesvirus infection included maximal daily number of vomiting, maximal increase of body temperature, time of onset of catarrhal symptoms since beginning of disease, level of ketone bodies in urine, amount of leukocytes, rod-shaped neutrophils and eosinophils in common blood count during acute phase of disease. As a reference group, we used respective clinical and paraclinical indices of patients with rotavirus infection only. Accuracy of model is 81.73 %.